2002
DOI: 10.1016/s0008-6363(01)00510-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific differences of cardiac remodeling in subjects with left ventricular dysfunction: a population-based study

Abstract: Men with moderate or severe LV dysfunction are characterized by an increase in both LV mass and cardiac natriuretic peptide plasma concentrations. In contrast, LV mass and natriuretic peptide concentrations increase to a lesser extent and only with severe LV dysfunction in women. These observational data suggest gender-specific control of myocardial adaptations to hemodynamic overload and a more rapid induction of LV hypertrophy during myocardial dysfunction in male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 32 publications
6
79
2
1
Order By: Relevance
“…Results from our study indicate that myocytes from female FVB mice were characterized by a significantly reduced peak shortening and maximum rate of shortening= relengthening, and a longer duration of relengthening as compared to male counterparts. This was consistent with some studies that showed a weaker contractile function in female hearts (10). Furthermore, the gender difference was significantly augmented in older FVB mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results from our study indicate that myocytes from female FVB mice were characterized by a significantly reduced peak shortening and maximum rate of shortening= relengthening, and a longer duration of relengthening as compared to male counterparts. This was consistent with some studies that showed a weaker contractile function in female hearts (10). Furthermore, the gender difference was significantly augmented in older FVB mice.…”
Section: Discussionsupporting
confidence: 93%
“…Recent clinical, epidemiological and experimental evidence has convincingly suggested that there is a gender bias in the progression of diabetic cardiomyopathy. In general, while difference in cardiac rhythm and arrhyathmia exists between genders, premenopausal women are much less susceptible to heart failure, and display much more favorable myocardial adaptation to hemodynamic overload both in contractile function and hypertrophic reserve (8)(9)(10)(11)(12)(13)(14). However, this ''gender-bias'' or ''female advantage'' may be significantly dampened with the onset of diabetes in pre-menopausal women (15).…”
Section: Introductionmentioning
confidence: 99%
“…extracellular matrix remodeling; ovariectomy; gender; hypertrophy; hormone; collagen; MT1-MMP; ventricle THE RISKS AND BENEFITS ASSOCIATED with estrogen replacement therapy remain uncertain. Conflicting results regarding the effect of estrogen replacement on the outcome of cardiovascular disease have been obtained from population studies, animal models, and clinical trials (2,16,20,21,32,33,61). The inconsistency of these findings demonstrates the lack of understanding of the mechanisms by which estrogen exerts its beneficial effects on the cardiovascular system.…”
mentioning
confidence: 99%
“…However, it is of note that in the general population, elevated plasma BNP was associated with a greater likelihood of future blood pressure increase only in men. 14 In addition, Luchner et al 15 showed that plasma BNP concentrations are much better correlated to left ventricular mass and function in men as compared with women. …”
Section: Hocher Et Al Relaxin Predicts Death In Men 2267mentioning
confidence: 99%